PELATIHAN MENYUSUN PROPOSAL PENELITIAN TINDAKAN KELAS (PTK) BAGI GURU DI SMA NEGERI 1 GELUMBANG - Deskoni; Rusmin AR; Ikbal Barlian; Firmansyah (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2020)
This dedication was carried out in SMA 1 Gelumbang, with a target audience of 30 teachers with different subjects. The service model used is a mentoring model with technical assistance methods in making class action research proposals for different subjects which are carried out by means of socialization regarding the nature of class action research to the technical preparation of proposals conducted over two days. The purpose of devotion is to produce a product in the form of a class action research proposal. Evaluation of activities is carried out with tests and product assessments. The results of the initial knowledge test about the nature of classroom action research are 7.04 on average, increasing to an average of 8.96 on the final knowledge test. Improved test results by 0.43 with the moderate category. The product evaluation made by the target audience shows that the products made are included in the good category with a value of 77.42%. With this service, it is expected that in the future it can contribute to teachers in the form of knowledge and skills in making class action research proposals.